Karakteristik Konsumen Pada Pusat Jajanan di Yogyakarta - Ayuningtyas, Cita Eri (Gastronary, 2024)
The culinary industry is growing rapidly. The marketing strategy carried out by the owners to attract buyers' interest is not only limited to products, but also the place for example in busy centers such as Pasar Tiban /night market. Pasar Tiban/night market serves a variety of culinary delights such as traditional culinary snacks to international snacks and called to street food. Some of Pasar Tiban /night markets in Yogyakarta include Alun-alun Kidul, Sultan Agung Stadium, or Sunday morning (Sunmor) UGM. Consumers come not only from local communities but also outside the city. The large number of consumers get the information about culinary delights from social media or environmental influences. The various culinary delights sold at Alkid and Sunmor are quite varied, from traditional to foreign culinary delights. It makes culinary enthusiasts Pasar Tiban in Yogyakarta having various characteristics. This research aims to analyze the characteristics of culinary consumers in culinary center in Yogyakarta. This research design is quantitative research with a survey. The subjects recruited by accidental sampling. The results show that the majority of culinary center consumers are female consumers (89.1%), 21-30 years old (56.3%), almost of the respondent are students (82.7%), their education is in the diploma/bachelor (75 .5%), and the distance between residence and location is more than 3 km (63.6%). So, it can be concluded that culinary consumers in the busy center of Yogyakarta are dominated by female consumers and others characteristic.